Neighbours in the City: 'Four Animal Spirits' in Beijing from the 19th Century to the Present - Ju, Xi (Religions, 2023)
In northern China, four animals—the fox, weasel, hedgehog, and snake—are commonly believed to have the magical power of immortality, and they are referred to as the Four Animal Spirits (四大门, sidamen). Researchers have regarded these spirits as part of a form of shamanism, but what I learned from my fieldwork in Beijing suggests a different understanding. From the 19th century to the present day, many inhabitants of Beijing have consistently believed that the Four Animal Spirits have their own personalities, intentionalities, and social organisation. They can change their status through self-cultivation, and they share the city with humans, who are their neighbours. As humans can understand animals, these animals can understand humans and respond rationally to changes happening in the world. These beliefs are not unique to Beijing’s residents; indeed, similar ideas can be found in classical Chinese literature before the Han Dynasty (202–220 BCE); moreover, these beliefs differ significantly from the widely accepted theory of shamanism. Knowing about the Four Animal Spirits does not constitute a window into or a way of organising human societies; the Four Animal Spirits do not represent a cultural structure or deep unconsciousness. They provide knowledge about the relationship between humans and animals and entice people to learn about these animals, live with them, and, ultimately, construct a world in which humans and animals can coexist.